2008
DOI: 10.1088/0963-0252/17/2/024015
|View full text |Cite
|
Sign up to set email alerts
|

Corona initiated from grounded objects under thunderstorm conditions and its influence on lightning attachment

Abstract: Lightning attachment to grounded structures due to the initiation of an upward connecting leader from them is considered taking into account the effect of corona space charge near the structures. It is shown that the corona space charge strongly affects the initiation and development of the connecting leader. Specific features of a non-stationary corona are analysed analytically and numerically for one-dimensional electrode geometries and for a grounded rod coronating in a slowly varying thundercloud electric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 34 publications
4
63
0
Order By: Relevance
“…streamers and leaders). Extensive theoretical research on glow corona discharges from tall objects, and their effect on the initiation of streamers and upward leaders, has been published in the literature in recent years [5][6][7][8][9][10][11][12][13]. However, in all of these studies the analysis has been based on very simple models of the glow corona and the leader discharges.…”
Section: Aq1mentioning
confidence: 99%
See 2 more Smart Citations
“…streamers and leaders). Extensive theoretical research on glow corona discharges from tall objects, and their effect on the initiation of streamers and upward leaders, has been published in the literature in recent years [5][6][7][8][9][10][11][12][13]. However, in all of these studies the analysis has been based on very simple models of the glow corona and the leader discharges.…”
Section: Aq1mentioning
confidence: 99%
“…Based on this conclusion, it was suggested that the glow corona might significantly reduce the efficiency of tall objects to intercept lightning flashes. Consequently, it was suggested that glow corona discharges might be practically utilized in the design of an unconventional lightning protection system [6,[11][12][13]. Such a system, usually known as a dissipation array, uses a uniform, umbrella-shaped array of needles, capable of generating a massive corona space charge [6,13].…”
Section: Aq1mentioning
confidence: 99%
See 1 more Smart Citation
“…in lamp ignition [6,7] as well as in the counter leaders stretching from tall structures upwards towards an approaching lightning leader [8].…”
Section: Introductionmentioning
confidence: 99%
“…The onset electric field for corona discharges is commonly determined by Peek's formula e.g. [8] which typically requires electric fields of the order of 3 MV/m. However, coronas has been observed to occur at lower electric fields as suggested by the AMS e.g.…”
Section: Evaluation Of Point Discharge and Coronamentioning
confidence: 99%